1997
DOI: 10.1007/bf00805440
|View full text |Cite
|
Sign up to set email alerts
|

Validity of the PAS-ADD for detecting psychiatric symptoms in adults with learning disability (mental retardation)

Abstract: The Psychiatric Assessment Schedule for Adults with Developmental Disability (PAS-ADD) is a semi-structured interview for use with respondents who have learning disability and for key informants. This report investigates the ability of the instrument to detect symptoms that had been found to exist during routine clinical assessment of the patients. Field trials involved 95 referred patients with learning disability and a key informant for each sample member. Clinical opinions of the referring psychiatrists wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(61 citation statements)
references
References 14 publications
1
59
0
1
Order By: Relevance
“…The measures used to measure the effects of traumatic events included the Developmental Behavior Checklist for Adults (DBC-A; Einfeld, Tonge, & Mohr, 2002;S13) Matson & Bamburg, 1998; S14); the Problem Behavior subsection of the Scales of Independent Behavior Revised (SIB-R; Bruininks, Woodcock, Weatherman, & Hill, 1996; S14); the PAS-ADD (Moss et al, 1997;S9); the PAS-ADD Checklist (Moss et al, 1998, S11, S12, and S7); the Anxiety, Depression and Mood Scale (ADAMS; Esbensen, Rojahn, Aman, & Ruedrich, 2003;S14); the Adaptive Behavior Schedule (Residential and Community; Nihira, Leland, & Lambert, 1993; S15); the Short Adaptive Behavior Scale (SABS; Hatton et al, 2001; S12); and the Prout-Strohmer Assessment System (PSAS; Strohmer & Prout, 1989;S8). In S2 the Mental Handicap Disability Assessment Scale (MHDAS; Colne, Shah, & Wing, 1982) was used.…”
Section: How the Effects Of Trauma Were Measuredmentioning
confidence: 99%
“…The measures used to measure the effects of traumatic events included the Developmental Behavior Checklist for Adults (DBC-A; Einfeld, Tonge, & Mohr, 2002;S13) Matson & Bamburg, 1998; S14); the Problem Behavior subsection of the Scales of Independent Behavior Revised (SIB-R; Bruininks, Woodcock, Weatherman, & Hill, 1996; S14); the PAS-ADD (Moss et al, 1997;S9); the PAS-ADD Checklist (Moss et al, 1998, S11, S12, and S7); the Anxiety, Depression and Mood Scale (ADAMS; Esbensen, Rojahn, Aman, & Ruedrich, 2003;S14); the Adaptive Behavior Schedule (Residential and Community; Nihira, Leland, & Lambert, 1993; S15); the Short Adaptive Behavior Scale (SABS; Hatton et al, 2001; S12); and the Prout-Strohmer Assessment System (PSAS; Strohmer & Prout, 1989;S8). In S2 the Mental Handicap Disability Assessment Scale (MHDAS; Colne, Shah, & Wing, 1982) was used.…”
Section: How the Effects Of Trauma Were Measuredmentioning
confidence: 99%
“…The more recent Psychiatric Assessment Schedule for Adults with a Developmental Disability (PAS-ADD; Moss et al, 1993b), developed by the Hester Adrian Research Centre, has been shown to have both reasonable reliability and validity (Costello et al, 1997;Moss et al, 1997Moss et al, , 1998Prosser et al, 1998). This makes it one of the most useful tools currently available for the identification and diagnosis of psychiatric disorder in adults with learning disability.…”
Section: The Pas-addmentioning
confidence: 99%
“…These difficulties have led some to adapt the standard DSM and ICD criteria for use with ID (King, DeAntonio, McCracken, Forness, & Ackerland, 1994;Szymanski & King, 1999). Others have designed interview schedules specifically for this population, including the Psychiatric Assessment Schedule for Adults with Developmental Disability (PAS-ADD or mini-PAS-ADD; Moss, Prosser, & Goldberg, 1996;Moss, Ibbotson, Prosser, Goldberg, Patel, & Simpson, 1997). Moss et al (1996) showed that direct interviews with both respondents and caregiver informants using these schedules with adults with ID reduces missed diagnoses.…”
Section: A Clinical-medical Approachmentioning
confidence: 99%